2015
DOI: 10.1182/blood-2015-03-633404
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of mutation profile and response in patients with myelofibrosis treated with ruxolitinib

Abstract: Key Points In patients treated with ruxolitinib, harboring ≥3 mutations was inversely correlated with spleen response and time to treatment discontinuation. Multigene profiling may be useful for therapeutic planning.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
134
1
10

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 176 publications
(152 citation statements)
references
References 37 publications
7
134
1
10
Order By: Relevance
“…However, in the same patient cohort as in the Newberry et al report, it was shown by using an enlarged mutation panel that those patients with 3 or more mutations at study entry were more likely to discontinue treatment early and had lower odds of achieving spleen response. 8 These latter findings suggest that patients with higher mutation complexity are less likely to obtain sustained responses to ruxolitinib, in line with findings that the number of mutations is independently associated with shorter survival and increased risk of leukemic transformation. 9,10 When deciding on initial treatment using ruxolitinib, the above molecular information represents green and yellow lights for starting the treatment (see figure).…”
Section: Alessandro M Vannucchi and Paola Guglielmelli University Ofsupporting
confidence: 69%
“…However, in the same patient cohort as in the Newberry et al report, it was shown by using an enlarged mutation panel that those patients with 3 or more mutations at study entry were more likely to discontinue treatment early and had lower odds of achieving spleen response. 8 These latter findings suggest that patients with higher mutation complexity are less likely to obtain sustained responses to ruxolitinib, in line with findings that the number of mutations is independently associated with shorter survival and increased risk of leukemic transformation. 9,10 When deciding on initial treatment using ruxolitinib, the above molecular information represents green and yellow lights for starting the treatment (see figure).…”
Section: Alessandro M Vannucchi and Paola Guglielmelli University Ofsupporting
confidence: 69%
“…35 In the present study, we observed a poorer MR rate on CALR mutant clones in patients harboring additional mutations, suggesting that molecular alterations in pathways such as epigenetics may hamper the efficacy of IFNa therapy. The presence of additional mutations such as ASXL1 has been reported to hinder the clinical response to ruxolitinib in MF patients, 36 an effect not observed in our cohort of ET patients treated with IFNa.…”
Section: Discussionmentioning
confidence: 49%
“…These data are reminiscent of the treatment of myelofibrosis (MF) with ruxolitinib for which the presence of mutations in ASXL1 or SRSF2 was also inversely correlated with spleen response, time to treatment discontinuation and shortened OS. 26 We found no evidence for additional KIT mutations that might be conferring resistance to midostaurin (data not shown).…”
Section: Discussionmentioning
confidence: 67%